Proposta de metodologia multicritério como ferramenta para formulação e execução de políticas públicas para barragens de mineração e indústria em Minas Gerais - Diogo Soares de Melo Franco (2019)
Minas Gerais, according to the National Water Agency (ANA, 2016), hold 43% of the mining tailings dams registered in the country. It is also the state with the largest history of large-scale accidents, resulting in deaths, contamination and various environmental impacts. To operate in the management and monitoring of these structures, the State Environmental Foundation - FEAM, an agency linked to the State Secretariat of Environment and Sustainable Development of Minas Gerais, and the National Department of Mineral Production - DNPM, a federal government body recently transformed in the National Mining Agency (ANM), have programs to monitoring the safety conditions of these structures. The present research aims to propose a new methodology for the management and monitoring tailings dams and industrial waste dams in Minas Gerais. For this, a multicriteria analysis method was used, which allows the use of factors considered relevant for the management of these structures, considering that these factors share the same space. Thus, the criteria considered in the model represent a comprehensive list of information associated with structures, including structural characteristics (height, volume), potential cumulative and synergistic effects and possible areas of impact in the event of a break. The preliminary results point to the feasibility of the proposal as a subsidy for decision-making process in the formulation and execution of public policies related to dams management, in particular, regarding environmental permits and licenses and inspection, as well as for the elaboration of specific regulations for the sector.